Hepatocellular Carcinoma with Chronic Hepatitis B and Non-Islet Cell Tumor Hypoglycemia: A Case Report: NICTH in HCC: A Case Report - Tjahjadi, Angela Kimberly; Maimunah, Ummi; Loho, Imelda Maria (Universitas Airlangga, 2024)
Non-islet cell tumor hypoglycemia (NICTH) is a rare paraneoplastic syndrome manifestation associated with hepatocellular carcinoma (HCC). This report details a case of a 20-year-old woman with HCC linked to untreated chronic hepatitis B. The patient presented with refractory hypoglycemia that was suspected to be NICTH. She also exhibited decreased consciousness with an initial blood glucose reading of 31 mg/dL. After the administration of intravenous dextrose solution, the patient's consciousness improved, yet intermittent hypoglycemic episodes persisted due to insufficient oral intake. The laboratory findings revealed low levels of insulin and C-peptide. The management of the patient included a continuous infusion of 5% dextrose solution, administration of corticosteroids, and adherence to a high-calorie complex carbohydrate diet. Despite presenting with significant right upper abdominal discomfort and weight loss, the patient was diagnosed with HCC at stage B, according to the Barcelona Clinic Liver Cancer (BCLC) Staging System. The stage was determined based on the presence of extensive multifocal lesions, which rendered surgical resection and transarterial chemoembolization (TACE) non-viable. Consequently, palliative treatment using lenvatinib and antiviral therapy with tenofovir were initiated. NICTH involves an increased insulin-like growth factor 2 (IGF-2) precursor processing by tumor cells, leading to heightened peripheral glucose utilization and persistent hypoglycemia. Although tumor resection is the most effective treatment for NICTH, it was not feasible in this case. This report emphasizes the importance of considering NICTH in the differential diagnosis of refractory hypoglycemia for non-diabetic patients. It also underscores the need for parenteral nutrition and corticosteroid therapy to maintain euglycemia. Highlights: 1. This case report details a rare clinical presentation of non-islet cell tumor hypoglycemia (NICTH) associated with hepatocellular carcinoma (HCC) and chronic hepatitis B in a young patient, adding to the limited documented cases of this paraneoplastic syndrome. 2. The report provides a thorough clinical description, extensive diagnostic workup, and comprehensive management strategies, offering valuable insights into the complexities and challenges in diagnosing and treating NICTH in HCC patients. 3. This case emphasizes the critical need for early detection and intervention in HCC, particularly in non-cirrhotic patients with chronic hepatitis B, and highlights the importance of considering paraneoplastic syndromes in the differential diagnosis of refractory hypoglycemia in non-diabetic patients.